Birth month and risk of skin tumors—Follow up of six million Caucasians born from 1950 to 2014 in Sweden - Rickard Ljung; Mats Talbäck; Amal R. Khanolkar; Maria Feychting (Cancer Medicine, 2020)
Abstract Background Some studies hypothesize that birth month—as a proxy of exposure to ultraviolet radiation in early infancy—is associated with increased risk of skin tumors. Methods We studied a national cohort of all 5 874 607 individuals born in Sweden to parents of Swedish or Nordic origin as a proxy for Caucasian origin, 1950 to 2014. The cohort was followed for incident skin tumors, including squamous cell carcinomas and melanomas but not basal cell carcinomas, through 2015 from birth up to age 65 for the oldest cohort. Cox regression estimated the association between month of birth and risk of skin tumors in models adjusted for sex, calendar period, and education. Crude observed to expected ratios were also calculated. Results There were 33 914 cases of skin tumors, of these, 3025 were squamous cell cancer, 16 968 malignant melanoma and 8493 melanoma in situ/other and 5 428 squamous cell in situ/other in 192 840 593 person‐years of follow‐up. Observed to expected ratios by month of birth showed no association between month of birth and risk of skin tumors, and the same result was seen when Cox regression analysis was used. Subgroup analyses by sex, educational level, calendar period, or age at follow‐up similarly showed no association. Conclusion This large register‐based cohort study showed no evidence of a higher risk of skin tumors in those born during the spring. Thus, this study lends no support to the hypothesis that birth during spring is a major risk factor for later skin tumors.